Depositional Environment of the Sangkarewang Oil Shale, Ombilin Basin, Indonesia - Komang Anggayana; Agus Haris Widayat; Sri Widodo (Institute for Research and Community Services, Institut Teknologi Bandung, 2014)
Five samples from 56 m long drill core of lacustrine Sangkarewang oil shale have been studied by means of petrography and organic geochemistry to investigate the organic matter composition and depositional environments of the shale. The organic matter consists of abundant lamalginite (30%, v/v) and very limited amount of vitrinite, suggesting aquatic depositional environments with minor terrestrial influence. Organic geochemical analysis exhibits the dominance of pristane, phytane, and generally n-alkanes compounds. These compounds might originate mostly from aquatic photosynthetic organisms. The oil shale was likely deposited in anoxic lake environments, suggested by the presence of framboidal pyrite (6%, v/v) and preserved organic matter with total organic carbon (TOC) about 4.9%. The pristane/phytane ratio is relatively high about 3.9 and thought as source sensitive rather than redox sensitive. Hopanoid and aryl isoprenoid compounds are present in minor amounts. The latter compounds are interpreted to be derived from green sulfur bacteria dwelling in anoxic and the presence of H2S in bottom water.